A study on the effectiveness of the advertising media used by Maybank for its financing services towards customer awareness in 2008 / Ida Aziaty Ramli - Ramli, Ida Aziaty (Faculty of Business and Management, 2008)
Advertising media is a medium advertisers' adopt as a channel of communication to communicate their products or services to the existing or potential customers. Advertising effectiveness depends on good media selection. Media decisions are typically based upon target customers, or usage measures. In the existing competitive market, many businesses from various backgrounds have been adopting these advertising media to help in creating awareness to the public of their existence and product or service offerings. Maybank as one of the leading financial institution in Malaysia also adopts these advertising medium as their communication channel. This study is conducted to identify which advertising media is effective in creating customer awareness towards Maybank financing services. The survey is conducted in Klang Valley as it targets the public in shopping malls mainly in Petaling Jaya, Subang Jaya and Damansara. The sample size for this study is 85 respondents above 18 years old who are randomly picked under convenience sampling. Data obtained using two methods that are primary and secondary data. Respondents are required to answer the questionnaires that include the statements regarding customer awareness, financing services, outdoor advertising, newspaper advertising, radio advertising and web/internet advertising. The data obtained is analyzed and summarized in a readable and easily interpretable form. The Statistical Package for the Social Science (SPSS) version 15.0 has been used to summarize the data. The results are in the form of reliability testing, frequency, correlation and descriptive statistics. Based on this research, the result indicates that there are significant relationship between all advertising media which include outdoor, newspaper, radio and web/internet advertising. In additional, based on the mean and standard deviation for each advertising media, the first rank that gives the highest effectivel1ess level according to their relationship with customer awareness is newspaper advertising. It is followed by the second rank which is web/internet advertising, third rank is outdoor advertising and lastly the fourth rank is radio advertising.